Perancangan UIUX Aplikasi Pemantau Kelembaban Tanah dan Suhu Udara Pada Tanaman Buah Naga - Sabila, Qolbi Sin; Tjen, Jimmy (MDP Student Conference, 2025)
The increase in the number of dragon fruit commodities is greatly influenced by the growth and quality of the plant itself. Soil moisture and air temperature are the main factors that must be considered by farmers in the cultivation of dragon fruit plants. There is a need for regular monitoring of dragon fruit plants to maximize the growth of these plants. This research aims to design a User Interface (UI) display for the application of monitoring soil moisture and air temperature in dragon fruit plants. This application is based on Android to be more flexible when used. This monitoring application is supported by the use of IoT technology sensor devices connected to a microcontroller, this application can present real-time data about plant conditions, such as soil moisture levels and air temperature in a visual form that is easy to understand for users. The result of this research is a UI design with ease of providing information to users so that it can enable users to improve decision-making accuracy in monitoring soil moisture and air temperature in dragon fruit plants. This is expected to have a positive impact on the productivity of users in caring for dragon fruit plants and can maintain the quality of the harvest.